2021
DOI: 10.1002/pat.5257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of chemically crosslinked gelatin and chitosan to produce hydrogels for biomedical applications

Abstract: Gelatin and chitosan polysaccharides were chemically modified to get methacrylate functionality to obtain biocompatible hydrogels for use as tissue engineering scaffolds. The methacrylation reaction was verified by 1H‐NMR. The degree of methacrylation was varied from 7% to 40% by changing the molar ratio of polysaccharide to methacrylic anhydride and the type of polysaccharide utilized. After the modification, polysaccharide‐based hydrogels were prepared by free‐radical polymerization in the presence of UV lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…Hydrogels were formulated in different batches using a free radical polymerization method that involved grafting monomers onto polymer networks [ 46 ]. Chitosan (natural polymer) solutions were prepared with (1% w/v) aqueous acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrogels were formulated in different batches using a free radical polymerization method that involved grafting monomers onto polymer networks [ 46 ]. Chitosan (natural polymer) solutions were prepared with (1% w/v) aqueous acetic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture was dialyzed (MWCO 6–8 KDa) against ultrapure water at 25 °C, freeze‐dried, and stored for further use. [ 37 ]…”
Section: Methodsmentioning
confidence: 99%
“…The secretion of bioactive factors from ADSCs promoted wound healing by ADSCs/PVA hydrogel. Joshi et al 84 evaluated the wound healing ability of fibroblast cells loaded in hybrid gelatin‐chitosan hydrogels. The hybrid gelatin‐chitosan hydrogels were prepared via chemical modification to get methacrylate functional groups.…”
Section: Stem Cell Based Hydrogel Therapymentioning
confidence: 99%
“…Moreover, the in vivo results indicated that the gelatin hydrogels combined with ADSCs and its culture medium could potentially accelerate the wound healing process in both mouse and porcine models 84 evaluated the wound healing ability of fibroblast cells loaded in hybrid gelatin-chitosan hydrogels. The hybrid gelatinchitosan hydrogels were prepared via chemical modification to get methacrylate functional groups.…”
Section: Stem Cell Based Hydrogel Therapymentioning
confidence: 99%